Isolation, Molecular Characterization And Predatory Activity Of Two Indian Isolates Of Nematode-Trapping Fungi (Applied Biological Research, 2023)
Two nematode trapping fungi were isolated from the arable soil samples  collected from district Anand (Gujarat) India and identified on the basis  of their culture-morphological characteristics and 18S rRNA gene  sequencing as Arthrobotrys conoides (GenBank accession No. JX979095)  and Duddingtoniaflagrans (GenBank accession No. JX979094). These  fungal isolates were assessed for their trapping efficiency against root  knot diseascausing nematode Meloidogyne spp., isolated from the  infected tomato plants. When incubated with nematodes for 24 hr, the  trapping efficiency of A. conoides and D. flagrans was 92-95 and 22- 29%, respectively. Growth conditions with respect to medium,  temperature and pH were also optimized. This study showed that A.  conoides is a promising candidate to control root-knot nematodes.  Phylogenetic relationship with other nematophagous fungi showed that  isolates formed monophyletic clade with other nematode trapping fungi  as well.
Keywords: Arthrobotrys conoides; biocontrol; Duddingtonia flagrans; Meloidogyne; nematophagous fungi